Analysis of Legal Urgency of Premarriage Agreements Related to Gono Gini's Assets in Ternate Religious Court - Jumriyani Jumriyani; Rusdin Alauddin; Baharuddin HI (LEGAL BRIEF, 2022)
The importance of a prenuptial agreement is closely related to the legal consequences that arise with the existence of marriage, namely, regarding assets, obligations of husband and wife and also the future of children born from marriage. Marriage has three legal consequences, namely, the existence of a legal relationship, the existence of assets and obligations to the children who are born and as a result of marriage including the existence of property and mixing of the property of both parties (husband and wife) which is known as innate property. , joint property, acquisition property and inheritance. The regulation regarding the protection of marital property of husband and wife in the form of a marriage agreement has been mandated by the legislation which has been explained comprehensively in the Civil Code. This study aims to determine the legal urgency of prenuptial agreements related to property gono gini at the Ternate Religious Court. This study uses a normative research method with an approach to legislation. The results show that the urgency of the prenuptial agreement law is to regulate the legal consequences of marriage, including the separation of assets obtained before marriage. In addition, the prenuptial agreement can also be about the separation of debts that occur before marriage, during the marriage, after divorce, and even death.